BUDAYA KONSUMERISME DALAM IKLAN SHOPEE VERSI CETAR MEMBAHANA - Heri Davidson; Dian Novitasari (Universitas Bunda Mulia, 2022)
The culture of consumerism forms a social space in which consumers are designed to live socially so that they follow the flow of signs, meanings, images and identities that flow endlessly.Â In this situation, consumer lifestyles are more towards consumptive lifestyles, which are never satisfied with something they already have.The theory used in this research is the theory of Roland Barthes's semiotics.Â In this research, the researcher will focus on the